In-Vitro Quality Evaluation and Comparative Analysis of Five Diclofenac Sodium Tablet Brands Marketed in Hodeida, Yemen - Faquih, Abdulgabar Ahmed; Alwesabi, Ali Saad; Abary, Mohammed; Areqi, Abdullah; Alkershi, Faheem Ahmed; Al-Haddad, Mohammed Gameel (University of Science and Technology, Yemen, 2025)
Background: In developing countries like Yemen, political instability and economic sanctions have led to compromised pharmaceutical quality control. Objective: This study aimed to evaluate and compare the quality control tests of five brands of enteric-coated 50 mg diclofenac sodium (DS) tablet formulations on the Yemeni market. Methods: Physical parameters such as diameter, thickness, hardness, friability, disintegration time, dissolution profile, and assay were evaluated. Validated UV spectroscopic and RP-HPLC methods assessed accuracy, linearity, and precision and were used to determine the drug content. Each brand was tested according to pharmacopeial standards for solid oral dosage forms. All tested brands (coded DS1DS5) conformed to pharmacopeial specifications. Results: Weight variation ranged from 1.010.29% to 2.010.14%, with hardness between 58.9 2.21 N and 146.10.7 N. Potency results from UV and HPLC methods were statistically similar with the paired test. The potency values ranged from 92.68% to 100.51%. Friability assessments showed less than 1% mass loss in all samples, adhering to USP limits. Disintegration times averaged ? 20 minutes across brands. In vitro drug release after 2 hours in 0.1 N HCl was minimal drug release (2.550.24% to 4.470.31%), indicating limited dissolution in gastric conditions, while in phosphate buffer (pH 6.8), all formulations released over 90% of the drug within 60 minutes, indicating efficient release of the drug in the more alkaline environment of the intestine. Conclusion: The evaluated diclofenac sodium tablets marketed in Yemen met pharmacopeial standards and possessed the quality parameters necessary for effective therapeutic use.